How much more the customers are willing to pay for higher level of service? An air transport study - Mansor, Rafizah; Jaafar, Ibnu Affan; Sallehudin, Fatin Aqilah (2012)
The research aims to investigate the relationship between customer satisfaction and the willingness of customer to pay for higher level of service provided by the Air Asia.Secondary data is used to measures the service quality and readiness of pay for higher service level in Air Asia. Results show that willingness of customer to pay is positively influenced by the customer’s satisfaction and also service quality in airlines industry. But the service quality needs to be highlighted as well as can improve the performance of the management itself.